Fine coal desulphurization and microwave energy absorption behaviour by microwave magnetic separation. (31st January 2017) - Zhang, Bo; Zhou, Chenyang; Zhao, Yuemin; Cai, Luhui; Fan, Xuchen
Abstract: Microwave energy has been used to improve the coal‐pyrite magnetism, while magnetic medium has been added to enhance the microwave energy. Hence, there will be a secondary gradient magnetic chain, which can improve the desulphurization process through magnetic separation. Microwave energy and medium synergistic effects are able to readily improve the magnetic desulphurization process for fine coal. The present paper has studied the impact of microwave energy on the magnetic desulphurization process for fine coal. Intrinsic electromagnetic parameters of different materials were used to analyze and predict the equivalent dielectric parameters of the fine coal layer. The electromagnetic parameter according to the effective medium theory equation for fine coal was established. Coal specific susceptibility is related to pyrite content and pyrrhotite content in pyrite. The specific susceptibility values for the three types of coals were found to be in the following order: Lu'an (LA) coal > Weinan (WN) coal > Yiluo (YL) coal. The most suitable value for LA high‐sulphur coal's sulphur content after being separated by dry type rare earth roll strong magnetic separator appeared to be 60 s delayed in nitrogen atmosphere compared to the corresponding value in an air atmosphere. LA fine coal sulphur content reduced to 2.05 % from 3.66 %, and the microwave magnetic separation desulphurization rate was 44 %.